Impact of anxiety symptoms on outcomes of depression: an observational study in Asian patients - Novick D; Montgomery W; Aguado J; Peng X; Haro JM (Neuropsychiatric Disease and Treatment, 2016)
Diego Novick,1 William Montgomery,2 Jaume Aguado,3 Xiaomei Peng,4 Josep Maria Haro3 1Eli Lilly and Company, Windlesham, Surrey, UK; 2Eli Lilly Australia Pty Ltd, West Ryde, NSW, Australia; 3Parc Sanitari Sant Joan de Déu, CIBERSAM, Universitat de Barcelona, Barcelona, Spain; 4Eli Lilly and Company, Indianapolis, IN, USA Objective: To investigate the impact of anxiety symptoms on depression outcomes in Asian patients with major depressive disorder (MDD) (n=714). Methods: The 17-item Hamilton Depression Scale (HAMD-17), overall severity, somatic symptoms, and quality of life (QOL) (EuroQOL Questionnaire-5 Dimensions [EQ-5D]) were assessed at baseline and 3 months. Anxiety was measured using items 10 and 11 from the HAMD-17. Linear, tobit, and logistic multiple regression models analyzed the impact of anxiety symptoms on outcomes. Baseline anxiety was related to age and the presence of pain symptoms at baseline. Results: Regression models showed that a higher level of anxiety was associated with a lower frequency of remission and lower QOL at 3 months. Patients with lower baseline anxiety symptoms had higher remission rates (odds ratio for each point of anxiety symptoms, 0.829 [95% confidence interval [CI]: 0.723–0.951]). Patients with higher levels of baseline anxiety had a lower QOL at 3 months (a decrease in EQ-5D tariff score for each point of anxiety symptoms, 0.023 [95% CI: 0.045–0.001]). Conclusion: In conclusion, the presence of anxiety symptoms negatively impacts the outcomes of depression. Keywords: depression, anxiety, Asia, observational, outcomes